Aptamer density dependent cellular uptake of lipid-capped polymer nanoparticles for polyvalent targeted delivery of vinorelbine to cancer cells. Issue 22 (6th February 2015) - Liu, Zhenbao; Zhao, Huanzhe; He, Lingyun; Yao, Yao; Zhou, Yanbin; Wu, Jianping; Liu, Juewen; Ding, Jinsong
Abstract : In this work, MUC1 aptamer (designated S2.2) modified and vinorelbine (VRL) loaded lipid-polymer hybrid nanoparticles (Apt-VRL-NPs) were prepared. Abstract : In this work, MUC1 aptamer (designated S2.2) modified and vinorelbine (VRL) loaded lipid-polymer hybrid nanoparticles (Apt-VRL-NPs) were prepared. Their cancer cell targeting efficiency and cell growth inhibition activity were investigated. The S2.2 aptamer was covalently linked to 1, 2-distearoyl- sn-glycero -3-phosphoethanolamine- N -carboxy(polyethylene glycol)2000 (DSPE-PEG2000 -COOH) using EDC/NHS coupling to obtain a DSPE-PEG2000 -Apt conjugate. The nanoparticles were then fabricated by a self-assembly method, using poly lactic- co -glycolic acid (PLGA) as the core and lipids (lecithin and DSPE-PEG2000 -COOH and DSPE-PEG2000 -Apt) as the shell. By adjusting the molar ratio of the DSPE-PEG2000 -Apt conjugate to total DSPE materials (DSPE-PEG2000 -Apt and DSPE-PEG2000 -COOH), nanoparticles with different aptamer densities were obtained. Transmission electron microscopy (TEM) indicates that the particles are spherical. Dynamic light scattering (DLS) measures the average diameter to be below 170 nm and the zeta-potential to be around −30 mV. The VRL encapsulation efficiency was between 50% and 60%. The accumulative VRL released into PBS (pH 7.4) over 108 h was lower than 50%, indicating a sustained release characteristic. The nanoparticle uptake efficiency was significantly higher in MUC1 overexpressing breast cancer cells (MCF-7) than in MUC1 negative cells (HepG2) as demonstrated by fluorescence microscopy and by quantitative fluorescence measurement. The MCF-7 cell targeting efficiency is enhanced with increased density of the S2.2 aptamer. The in vitro cell inhibition study shows enhanced toxicity of the S2.2-modified nanoparticles.